Influence of the operating conditions and the external mass transfer limitations on the synthesis of fatty acid esters using a Candida antarctica lipase - Trubiano, G.; Borio, Daniel Oscar; Errazu, Alberto Felipe (Enzyme and Microbial Technology)
The enzymatic esterification of fatty acids (mainly oleic acid) and ethanol is studied in this work. The reactions are catalyzed by commercial immobilized lipases from Candida antarctica (Novozyme 435) and are carried out in a batch reactor at solvent free conditions. The influence of several important reactions conditions as temperature, initial molar ratio, initial water percentage, and enzyme percentage on the equilibrium conversion and the initial reaction rates is carefully analyzed. A non-linear relationship is established between the initial reaction rates and the enzyme percentage. An optimum value of the initial molar ratio is detected for each enzyme percentage and the effect of inhibition by alcohol is confirmed. Under the studied conditions, it is demonstrated that the influence of the external mass transfer resistance on the reaction rate is not significant. Therefore, the experimental data are appropriated for kinetic modeling purposes. Fil: Trubiano, G. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Bahía Blanca. Planta Piloto de Ingeniería Química. Universidad Nacional del Sur. Planta Piloto de Ingeniería Química; Argentina Fil: Borio, Daniel Oscar. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Bahía Blanca. Planta Piloto de Ingeniería Química. Universidad Nacional del Sur. Planta Piloto de Ingeniería Química; Argentina Fil: Errazu, Alberto Felipe. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Bahía Blanca. Planta Piloto de Ingeniería Química. Universidad Nacional del Sur. Planta Piloto de Ingeniería Química; Argentina